Forced Displacement, Gender, and Livelihoods : Refugees in Ethiopia - Admasu, Yeshwas (World Bank, Washington, DC, 2021)
This study uses the Ethiopia Skills Profile Survey (2017) to examine the gender differences in livelihood opportunities and activities between refugees and host communities. The results show that refugees are significantly less likely to be in employment, and that household characteristics influence women’s economic opportunities. While having a female household head, access to agricultural land, and the number of female adults increased female participation in economic activities, conversely, higher numbers of children in the household significantly reduce women’s opportunities. Higher education attainment boosts both male and female refugees’ participation in wage employment. Among refugees, Somali refugees have relatively better access to employment opportunities compared to other refugee groups, especially refugees from South Sudan and Sudan.